The influence of new SARS-CoV-2 variant Omicron (B.1.1.529) on vaccine efficacy, its correlation to Delta variants: A computational approach. (August 2022) - Ranjan, Prashant; Neha; Devi, Chandra; Devar, Kaaviyapriya Arulmozhi; Das, Parimal
Abstract: The newly discovered COVID variant B.1.1.529 in Botswana has more than 30 mutations in spike and many other in non-spike proteins, far more than any other SARS-CoV-2 variant accepted as a variant of concern by the WHO and officially named Omicron, and has sparked concern among scientists and the general public. Our findings provide insights into structural modification caused by the mutations in the Omicrons receptor-binding domain and look into the effects on interaction with the hosts neutralizing antibodies CR3022, B38, CB6, P2B–2F6, and REGN, as well as ACE2R using an in silico approach. Computational analysis revealed that the Omicron variant has a higher binding affinity for the human ACE2 receptor than the wild and Delta (AY.1 and AY.2 strains), but lower than the Delta AY.3 strain. MD simulation and docking analysis suggest that the omicron and Delta AY.3 were found to have relatively unstable RBD structures and hampered interactions with antibodies more than wild and Delta (AY.1 and AY.2), which may lead to relatively more pathogenicity and antibody escape. In addition, we observed lower binding affinity of Omicron for human monoclonal antibodies (CR3022, B38, CB6, and P2B2F6) when compared to wild and Delta (AY.1 & AY.2). However, the binding affinity of Omicron RBD variants for CR3022, B38, and P2B2F6 antibodies is lower as compared to Delta AY.3, which might promote immune evasion and reinfection and needs further experimental investigation. Graphical abstract: Image 1 Highlights: In silico analysis of structural changes of variants & interaction with the host's neutralizing antibodies and ACE2R. The higher binding affinity of Omicron's RBD for the ACE2 receptor was observed. Lower interactions of Omicron with human neutralizing antibodies were found. The relatively unstable RBD structures of Omicron and Delta AY.3 are supposed to cause more pathogenicity. This study suggests that the Omicron variant may promote immune evasion and chances of re-infection.